The effect of branching deregulation on finance wage premium - Ahmet Ali Taskin; Firat Yaman (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2023)
What is the role of financial deregulation on rising finance wage premium in the US? This study makes use of the Interstate Banking and Branching Efficiency Act of 1994 as an exogenous shift to local banking markets and investigates the effect of deregulation induced competition on relative wages in finance. We find that the finance wage premium increased significantly in deregulated states. Our estimates suggests that the deregulation explains about a quarter of the increase in finance wage premium between 1994 and 2008.
Keywords: 330